Perbedaan Kecepatan Pengembangan Paru Sebelum dan Sesudah Latihan Pernapasan Diafragma dalam Upaya Mempercepat Pelepasan Water Seal Drainage (WSD) - Rosalina Rosalina; Sukarno Sukarno; Yunita Galih Yudanari (Program Studi S1 Keperawatan Universitas Ngudi Waluyo, 2018)
An Pleural effusion is an excessive accumulation of fluid, blood or water in the pleural cavity which will cause the increase of shortness of breath because of the decreasing space for lung expansion. One of the efforts to reduce the complaints of shortness of breath is by insertion of water seal drainage. Water Seal Drainage (WSD) is a medical action performed to remove air or fluid from the pleural cavity. The patient's ability to breathe effectively is an indicator to release WSD. This study generally aims to determine the effectiveness of diaphragmatic breathing exercises on the speed of lung expansion in patients with water seal drainage insertion. The research design was pre experiment with pre test - post test group design. The population in this study were patients with insertion of WSD who were admitted to Dr. Muwardi Surakarta Hospital. The sampling technique was purposive sampling. The number of samples were 16 respondents. To measure lung expansion, the indicator used Peak Expiratory Flow Rate as measured by peak flow meter. Data analysis used dependent t-test. The results show that there are differences in the speed of lung expansion in patients with WSD insertion before and after diaphragmatic breathing exercises with p-value of 0.0001. Suggestion for nurses to be able to train diaphragmatic breathing exercise in patients with WSD insertion increase lung expansion so that WSD can be released and the risk of infection can be reduced.